The three roles of school leaders in maximizing the impact of Professional Learning Networks: A case study from England. (2020) - Brown, Chris; Flood, Jane
Highlights: Professional Learning Networks (PLN) are effective in fostering school improvement. To generate sustained change, PLNs require effective support from school leaders. Leaders need to formalise, prioritise and mobilise PLN engagement to achieve impact. Abstract: Professional Learning Networks (PLN) are considered to be an effective way to foster school improvement. To generate sustained change, PLNs require effective support from school leaders, but the actions school leaders might engage in to provide this support are little understood. To address this knowledge gap, this paper presents a case study of how senior leaders attempted to maximise the effectiveness of participating in one PLN in England. In-depth semi-structured interviews as well as impact data and policy documents, were used to ascertain the practices employed by school leaders to maximise the benefits of PLN engagement as well as their theeffectiveness. The authors argue that leaders need to effectively formalise, prioritise and mobilise PLN engagement for sustainable impact to materialise.